1987
DOI: 10.1016/0014-5793(87)80680-4
|View full text |Cite
|
Sign up to set email alerts
|

Unimpaired coupling of phosphorylated, desensitized β‐adrenoceptor to Gs in a reconstitution system

Abstract: Heterologous desensitization of turkey erythrocyte β‐adrenoceptors correlates with receptor phosphorylation and impaired receptor‐Gs coupling, as assessed by fusion of purified desensitized receptors with X. laevis erythrocytes [(1984) Science 225, 837‐840]. We have purified β‐receptors from desensitized and untreated turkey erythrocytes and have compared the abilities of these two receptors to couple with pure turkey erythrocyte Gs in a reconstituted system. Functional receptor‐Gs coupling was assessed by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…although it did not affect the interaction between non-phosphorylated rhodopsin and transducin (Wilden et al, 1986). In addition, Keenan et al (1987) reported recently that phosphorylated P-adrenergic receptors, which were purified from desensitized membranes with reduced receptor-(;, coupling, may couple with G, in a reconstituted system, and they suggested the contribution of a component(s) such as arrestin.…”
Section: Reconstitution Of Muscarinic Receptors and G Proteinsmentioning
confidence: 89%
“…although it did not affect the interaction between non-phosphorylated rhodopsin and transducin (Wilden et al, 1986). In addition, Keenan et al (1987) reported recently that phosphorylated P-adrenergic receptors, which were purified from desensitized membranes with reduced receptor-(;, coupling, may couple with G, in a reconstituted system, and they suggested the contribution of a component(s) such as arrestin.…”
Section: Reconstitution Of Muscarinic Receptors and G Proteinsmentioning
confidence: 89%
“…For rhodopsin, RK phosphorylation alone inhibits coupling to G t , and the intrinsic inhibitory effects of phosphorylation on coupling are augmented by the addition of arrestin (13,14). But for the ␤ 2 AR, neither in vitro phosphorylation by ␤ARK (GRK2) (15,16) nor in vivo desensitization by agonist (17) has a large effect on reconstituted receptor coupling. In contrast, phosphorylation of the ␤ 2 AR by protein kinase A does deactivate the receptor (16), as does addition of ␤-arrestin to ␤ARK1-phosphorylated ␤ 2 AR (18).…”
mentioning
confidence: 99%